Development of 3D Crane PID Controller System via State-space Approach - Zailan, Nur Zuhdi (Universiti Teknologi Petronas, 2011)
This progress report is basically present the research that has been done so for far based on the chosen topic, which is Development of 3D Crane PID Controller System via State-space Approach. The objective of the project is to be able to determine the 3D Crane and 2D Crane dynamics using the state-space approach and applies the Proportional-Integral-Derivative controller algorithm into the system for improvement. This dynamic equation is important for simulating the 2D crane in computer using Matlab and Simulink: software and designing a suitable controller for the 2D crane. The mathematical equation for 2D crane can be modeled dynamically using various approaches such as Lagrange-Euler's Method and Newton-Euler's Method. After the success of producing the 2D Crane dynamics, the mathematical formulation of 3D Crane dynamics will take place. Using the appropriate approach, the mathematical or state space equation of the 3D Crane dynamics will be produced for simulation in Matlab and Simulink Sofware. Finally, the Proportional-Integral-Derivative controller will be added into the system for increasing of crane reliability and productivity.